2000
DOI: 10.1093/geront/40.4.449
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for Surrogate Decision Makers, Informal Communication, and Advance Directives Among Community-Dwelling Elders

Abstract: This study, drawing on a nationally representative sample of community-dwelling adults aged 70 and older from the second wave of the Asset and Health Dynamics Among the Oldest Old (AHEAD) survey, addresses the need for greater information on advance care planning among older adults. Older persons expect to draw on a diverse array of persons to make health care decisions for them when they are unable to do so, including spouses, when available, as well as younger generation members such as children and grandchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
161
6
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(178 citation statements)
references
References 21 publications
10
161
6
1
Order By: Relevance
“…We hypothesized that acceptability outcomes might differ by literacy and language because lower education and minority status have been associated with low advance directive completion rates (9,(22)(23)(24) In addition, prior to this study, literacy and language appropriate advance directives with culturally diverse, text-enhancing graphics were not available. Therefore, we hypothesized that the greatest gains in the acceptability outcomes may be found in Spanish-speakers and subjects with limited literacy as these subjects may not have been previously exposed to an advance directive they could read or understand.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesized that acceptability outcomes might differ by literacy and language because lower education and minority status have been associated with low advance directive completion rates (9,(22)(23)(24) In addition, prior to this study, literacy and language appropriate advance directives with culturally diverse, text-enhancing graphics were not available. Therefore, we hypothesized that the greatest gains in the acceptability outcomes may be found in Spanish-speakers and subjects with limited literacy as these subjects may not have been previously exposed to an advance directive they could read or understand.…”
Section: Methodsmentioning
confidence: 99%
“…We hypothesized that participants would rate the redesigned advance directive easier to use and understand, more useful for personal treatment decisions, and more valuable for care planning. Because the hospital in which the redesigned advance directive was to be implemented has a large proportion of Spanish-speaking patients and patients with limited literacy, (20,21) and because engagement in advance care planning has been shown to be lower in minorities and subjects with lower education, (9,(22)(23)(24) we also explored whether the effects of the redesigned form were greater among participants with limited literacy and among Spanish-speakers.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of married older adults who name a DPAHC name their spouse Khodyakov 2007a, 2007b;Hopp 2000). When individuals do not legally appoint a surrogate, the appointment may occur by default.…”
Section: Study Aimsmentioning
confidence: 99%
“…Hopp (2000) analysed the Asset and Health Dynamics Among the Oldest Old (AHEAD) survey based on adults aged 70 and over. He found that white (as opposed to African American) participants were more likely to have produced advance directives.…”
Section: Nationality and Ethnic Background As Factors Affecting Surromentioning
confidence: 99%
“…Given that people who provide advance directives are more likely to receive the care that they prefer (Silveira et al, 2010), this implies that surrogate decision accuracy can be indirectly affected by ethnic background. Hopp's (2000) study could be extended by studying other ethnic groups and by using features other than ethnicity as a basis for comparison. For example, it would be interesting to compare nationalities or cultural groups that vary in terms of individualism and collectivism as these factors are likely to affect the way in which surrogates relate to beneficiaries (Tower, Kelly, & Richards, 1997;Zha, Walczyk, Griffith-Rose, Tobacyk, & Walczyk, 2006).…”
Section: Nationality and Ethnic Background As Factors Affecting Surromentioning
confidence: 99%